Mental Health of Combatants vs. Non-Combatants in Middle Eastern Conflicts: A Comparative Analysis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to comprehensively evaluate the psychological impact differences between individuals who served as combatants and those classified as non-combatants within the context of armed conflicts in the Middle East, through a meta-analysis of 47 independent studies involving a total of 28,463 participants and published between 2010 and 2024. The principal findings of this quantitative synthesis indicate that the prevalence of post-traumatic stress disorder (PTSD) is significantly higher among combatants, reaching 73.8%, compared to non-combatants, who reported a rate of 52.4%, with a large effect size (d=0.89, p<.001). Furthermore, results from multilevel regression analysis reveal that the duration of exposure to conflict is the strongest predictor of PTSD symptoms (β=0.67, p<.001), followed by the intensity of combat, which also contributes significantly (β=0.54, p<.001). In addition, major depression was documented in 64.2% of individuals within the combatant group and 48.7% among non-combatants, with an odds ratio of 2.34 and a 95% confidence interval ranging from 1.98 to 2.76. Anxiety disorders were also more prevalent among combatants, at 58.9%, compared to 41.3% in non-combatants, with a relative risk of 1.78 (p<.001). Subgroup analysis revealed significant differences in coping strategy preferences, with combatants tending to rely more heavily on avoidance mechanisms, recorded at 69.5% versus 45.2% among non-combatants. This meta-analytic finding expands upon the studies by Eltanamly et al. (2021) on war-induced trauma and by Figley & Nash (2011) regarding psychological defense mechanisms, with its distinct contribution lying in the identification of specific patterns of mental disorders influenced by individual roles within conflict dynamics. Overall, this research concludes that combatants exhibit a distinctive pattern of trauma manifestation and demonstrate a higher threshold of resistance to conventional therapeutic interventions, thus making a significant contribution to the formulation of role-based trauma treatment protocols in regions affected by armed conflict.